Research on integration of indoor and outdoor positioning in professional athletic training - Liu, Y.; Chen, Q. (Proceedings, 2018)
GNSS is widely used in professional athletic training as an outdoor location based services, and the indoor positioning technology has gradually flourished in the gymnasium. To keep up with the demand for athletic training in indoor and outdoor environment, integration of indoor and outdoor positioning technology can achieve a seamless indoor/outdoor position solution. The proposed method uses GPS/BEIDOU with IMU-MEMS technology for outdoor positioning and UWB with IMU-MEMS technology for indoor positioning to provide high precision positioning services. The experimental results show that the proposed method can achieve meter level position accuracy in outdoor environment and centimeter level position accuracy in indoor environment, it can provide precise and real-time positioning service for effective athletic training aid.